Business Plan sebagai Cermin Kognisi dan Perilaku Wirausaha: Pendekatan Psikologis dalam Perencanaan Bisnis - Zahra, Almaira Aura; Putri, Anggi Khoiriyyah; Cahyani, Zhika Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the business plan as a reflection of cognitive and behavioral processes in entrepreneurial psychology. The aim is to integrate psychological approaches into the understanding and formulation of business plans. Using a literature review method, this research explores how business planning shapes motivation, risk perception, and decision-making. The findings indicate that well-developed business plans are closely linked to self-efficacy, self-regulation, and entrepreneurs’ executive functioning. Additionally, technologies such as digital Business Model Canvas and AI tools support more systematic business planning. This study provides insight that applying psychological perspectives can enhance the effectiveness of business planning in facing the dynamic challenges of entrepreneurship.